Reactivity of Polysilazanes Allows Catalyst‐Free Curing of Silicones. Issue 9 (20th June 2022) - Sønderbæk‐Jørgensen, René; Meier, Sebastian; Dam‐Johansen, Kim; Skov, Anne L.; Daugaard, Anders E.
Abstract: Silicones are typically cured at room temperature by means of metal catalyst such as tin or platinum. When networks are formed, the catalyst becomes unrecoverable, which is of economic as well as environmental concern. Very few methods for producing metal catalyst‐free room‐temperature‐vulcanized (RTV) silicones exist and require conditions unavailable in industrial settings. Through the study of organic polysilazane (PSz) reactivity with simple alcohols by nuclear magnetic resonance, an unexpected fragmentation preference is discovered for breaking the SiN bond rather than the SiH; thereby, casting a new light on the fragmentation mechanism of PSzs. Utilizing the PSz fragmentation as a silyl ether coupling agent for multifunctional carbinol silicones, a method of producing catalyst‐free RTV silicone networks at ambient conditions is presented. These silicone networks are proven chemically similar to a standard condensation‐cured silicone and stoichiometric variations of PSz content demonstrate adjustable network properties. Abstract : The reactivity of polysilazanes (PSz) with a range of alcohols is investigated by nuclear magnetic resonance. This is exploited to prepare PSz curing silicones, where the PSz acts as a coupling agent that activates the condensation reaction, permitting metal catalyst‐free room temperature curing of room‐temperature‐vulcanized silicones.